The rise of featural modality in English - Cowper, Elizabeth (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 2013)
This paper takes a new look at the development of English modals as a syntactically distinct category (Lightfoot 1979; Roberts and Roussou 2003; van Gelderen 2003; Roméro 2005). Assuming that syntactic differences among languages are due to differences in the properties of elements of the functional lexicon (Chomsky 2000; Borer 2004, 2005a,b), I propose that the core of this syntactic change was the addition of a single feature, MODALITY, to the set of formal features characterizing the English Infl system. This feature was also added to the lexical entries of the verbs that became the English modals. Lightfoot (1979) refers to this class of verbs, prior to the change in question, as the premodals.